Sosialisasi Pemanfaatan Pekarangan Sebagai Sumber Pangan Dan Desa Ramah Lingkungan di Kabupaten Kediri - Irene Ratri Andia Sasmita; Devina Cinantya Anindita; Zupri Nur Cahyono (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2023)
Horticultural is one of the cultivation of plants utilizing yards. Horticultural commodities that can be planted in the yard include vegetables, fruits, biopharmaceuticals and ornamental plants. The use of yard land as a place for the cultivation of horticultural commodities has good benefits for meeting the food and nutritional needs of families. This is in line with the government program, Sustainable Food Courts (P2L). Activities that must be carried out by the government, both at the central and regional levels to fulfill family nutrition are to support activities that have the potential to improve healthy lifestyles with a variety of local foods so that people are healthier and more productive. The Sustainable Pangan Pekarangan Program is one of the activities to support stunting prevention to improve the quality of life. The socialization activity was carried out in Banjarejo Village, Ngadiluwih District, Kediri Regency. The aim of socializing the use of yards as a source of food and an environmentally friendly village is to empower residents in Banjarejo village to fulfil nutritious food by planting horticultural crops in their yards so that they can help prevent stunting and increase household income. From the results of the socialization, residents in Banjarejo Village were able to understand the process of planting lemon seeds and cultivating horticultural crops in their yards. Tanaman hortikultura merupakan salah satu budidaya tanaman dengan memanfaatkan lahan pekarangan. Komoditas hortikultura yang dapat ditanam di lahan pekarangan antara lain tanaman sayuran, buah-buahan, biofarmaka dan tanaman hias. Pemanfaatan lahan pekarangan sebagai tempat untuk budidaya komoditas hortikultura memiliki manfaat yang baik bagi pemenuhan kebutuhan pangan dan gizi keluarga. Hal ini selaras dengan program pemerintah, yaitu Pekarangan Pangan Lestari (P2L). Kegiatan yang wajib dilakukan oleh pemerintah, baik di tingkat pusat ataupun daerah untuk pemenuhan gizi keluarga adalah mendukung adanya kegiatan yang berpotensi meningkatkan pola hidup sehat dengan aneka ragam pangan local supaya masyarakat lebih sehat dan produktif. Program Pekarangan Pangan Lestari merupakan salah satu kegiatan dalam mendukung pencegahan stunting untuk meningkatkan kualiatas hidup. Kegiatan sosialisasi dilaksanakan di Desa Banjarejo, Kecamatan Ngadiluwih, Kabupaten Kediri. Tujuan sosialiasi pemanfaatan lahan pekarangan sebagai sumber pangan dan desa ramah lingkungan adalah memberdayakan warga di desa Banjarejo dalam pemenuhan pangan yang bergizi dengan menanam tanaman hortikultura dilahan pekarangan, sehingga dapat membantu dalam pencegahan stunting serta dapat meningkatkan pendapatan rumah tangga. Dari hasil sosialisasi, warga di Desa Banjarejo mampu memahami proses penanaman bibit lemon dan budidaya tanaman hortikulutura dilahan pekarangan.